Developing a Model of Women's Empowerment for Environmental Adaptation and Disaster Mitigation in Malang Regency - Ruli Inayah Ramadhoan; Krishno Hadi; Eka Kadharpa Utama Dewayani; Adi Hidayat Argubi (Sospol, 2023)
The damaged condition of the coastal forests in Malang Regency prompted the community to carry out conservation activities called the Green Belt Movement. This movement was initiated by the people around Sendang Biru, who are members of the Bhakti Alam Sendang Biru (BASB). The conservation movement has supported global efforts in climate change adaptation and disaster mitigation. Unfortunately, the movement is still lack of women involvement, but it is still dominated by men. This paper aims to reformulate the BASB green belt movement model by integrating gender mainstreaming in order to empowering local women in environmental adaptation and mitigation through conservation. The method used in this study is a qualitative approach with data collection techniques through interview, observation and literature study. As a form of empowering women through the Green Belt Movement by involving local women as the main actors, it is necessary to carry out intensive and massive counseling to construct awareness, provide positive affirmations and women's confidence. Furthermore, women communities’ institutionalization, increasing human resources through technical education and training programs and having economic benefits without ignoring ecological values are also considered to be necessary. Additionally, it is essential to encourage participation among stakeholders, especially government, to ensure the movement sustainability.